Les recherches autour de la reconstitution du trône de Napoléon au palais royal de Milan - Simone Percacciolo (Bulletin du Centre de Recherche du Château de Versailles)
This article tracks the different phases in the configuration of the Throne Room commissioned by Napoleon in the Royal Palace in Milan, the city that had become the capital of the new Kingdom of Italy. The analysis rests on two sources of particular importance – a project drawing by Luigi Canonica, the new architect of the Royal Household, and the 1814 inventory completed a few months after the collapse of the Napoleonic Kingdom of Italy – which provide a detailed description of the room. Other important references are drawn from elements found in the throne rooms of the Tuileries and Fontainebleau. The article also testifies to the commitment shown by the Royal Palace management team towards the restoration project and the historical-artistic development of the monumental interiors, in line with studies conducted in the early 2000s, and the hope of greater collaboration with France and international experts.